The Impact of Competency-Based Interviews on Employee Selection Results - Ading Rahman Sukmara (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2026)
Competency-based interviews have become crucial due to the shift in companies' need to recruit talent who are not only technically proficient but also excel in behavior (soft skills). The impact is an increase in the quality of selection results, allowing new employees to directly contribute to productivity and organizational goals. Research generally shows that competency-based interviews improve the quality of recruitment outcomes and employee performance compared to traditional methods. Overall, implementing competency-based interviews results in a more resilient, skilled, disciplined workforce, and higher job satisfaction. Competency-based interviews have a very positive and significant impact on employee selection results. This method results in more objective recruitment, improves person-job fit, enhances long-term performance, and strengthens the company's core competencies.